THE ASPECTS OF ENVIRONMENTAL LAW ENFORCEMENT IN INDONESIA AND THE IMPLEMENTATION OF INTERNATIONAL AGREEMENTS IN THE ENVIRONMENTAL FIELD IN INDONESIA - Hasyim, Yonani; Aprita, Serlika (Universitas Islam Negeri Raden Fatah Palembang, 2021)
Law enforcement is the process of enforcing or trying to implement legal norms as guides for traffic or legal relations in social and state life. In the environmental law enforcement system in Indonesia, there are three legal aspects described in the Environmental Protection and Management Act (UUPPLH), namely administrative law, civil law, and criminal law aspects. Where each aspect's law enforcement and law enforcement processes are distinct. The research method used was normative legal research. One component of environmental law enforcement is the use of civil law in environmental management. In the Environmental Protection and Management Act (UUPPLH) the process of enforcing environmental law through civil procedures is regulated in Chapter XIII Articles 84 to 93. In order to provide legal clarity in law enforcement, efforts are being made to solve environmental problems that emerge in Indonesia. Environmental law enforcement is an endeavor to ensure that regulations and requirements in general and specific legal provisions are followed and implemented through administrative, civil, and criminal supervision and enforcement. With the adoption of the first environmental rules, namely Law Number 4 of 1982 Concerning Basic Provisions for Environmental Management (UUKPPLH), government policy frameworks in implementing environmental law were actualized. Then, it was later replaced by Law Number 23 of 1997 concerning Environmental Management (UUPLH), which was subsequently replaced by Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) (Tude Trisnajaya, 2013: 2). The research method used in this study was normative juridical research, which means it was done with an eye on the laws, rules, and court decisions that were relevant to the topic. Keywords: Law Enforcement, Environment, Legal Norms, Dispute Resolution.